From Text to Knowledge: a Unifying Document-Centered View of Analyzed Medical Language - Zweigenbaum, P.; Bouaud, J.; Bachimont, B.; Charlet, J.; Séroussi, B.; Boisvieux, J.-F. (Methods of Information in Medicine, 1998)
Although medical language processing (MLP) has achieved some success, the actual use and dissemination of data extracted from free text by MLP systems is still very limited. We claim that the adoption of an ‘enricheddocument’ paradigm (or ‘document-centered’ view) can help to address this issue. We present this paradigm and explain how it can be implemented, then discuss its expected benefits both for end-users and MLP researchers.
Keywords: Natural Language Processing; Medical Language; Documents